Local knowledge and community behavior in the exploitation of parrots in surrounding area of aketajawe lolobata national park - M Nasir Tamalene; Said Hasan; K Kartika (Biosfer: Jurnal Pendidikan Biologi, 2019)
Parrots include in birds of Aves class and Psittaciformes order. In Indonesia, parrots in known by their local species names such as Nuri (true parrot), Kakatua (Cockatoo), and Perkici (Loriini). Parrots can be found almost in all type of habitat in Halmahera Island, Maluku Utara Province, from mangrove forest to tropical rainforest in lowlands and highlands in Halmahera Island. The research aims to describe community activities in the exploitation of parrots around the Aketajawe Lolobata National Park, Halmahera Island. The study uses the ex-post facto method with the questionnaire as the instrument to interview the communities consist of the catcher, seller, and owner of parrots. Research result data is analyzed descriptively and presented in the form of tables and charts. The result shows that there are five kinds of parrots that are caught, sold, and raised by the communities of Gitaraja, Bale, Koli, and Kosa Village. The exploited birds are Kasturi Ternate (Lorius garrulus) Nuri Kalung Ungu (Eos scuamata), Nuri Bayan (Eclectus roratus), Kakatua Putih (Cacatua alba) and Kakatua Jambul Kuning (Cacatua galerita). The number of parrots being caught during 2013-2016 is 327, 320 are sold, and 213 are raised. The highest percentage of parrot catching and selling is 21% in 2013, and the lowest is 2% in 2016-2018. The highest percentage of raising is 8% in 2015, and the lowest is 3% in 2018. Kasturi Ternate (Lorius garrulus) is the species with the highest rate of exploitation.